2014
DOI: 10.5455/msm.2014.26.366-371
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcome Following Hysteroscopic Treatment of Uterine Septum

Abstract: Background:Septate uterus is the most common uterine anomaly and a cause for miscarriage and infertility. Existing data suggested a better reproductive outcome of uterine septum following hysteroscopic septum resection.Objective:Current study was administered to share our experience in hystroscopic septum resection for reproductive outcome following hysteroscopic treatment of uterine septum and specifically focusing on different treatment protocols after hysteroscopic septum resection.Methods& materials:This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…[5][6][7] While Freud A at al, Selvaraj et al, Hollett-Caines J at al, Bakas et al and Esmaeilzadeh et al also found significant improvement in pregnancy rate (70-95%) after the septum resection. [8][9][10][11][12] Lee et al and Nesbitt-Hawes EM et al calculated the conception rate for infertile women with endometriosis after laparoscopic surgery. 13,14 They found overall pregnancy rate 41.9% and 73 % respectively after successful management of the endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] While Freud A at al, Selvaraj et al, Hollett-Caines J at al, Bakas et al and Esmaeilzadeh et al also found significant improvement in pregnancy rate (70-95%) after the septum resection. [8][9][10][11][12] Lee et al and Nesbitt-Hawes EM et al calculated the conception rate for infertile women with endometriosis after laparoscopic surgery. 13,14 They found overall pregnancy rate 41.9% and 73 % respectively after successful management of the endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopic resection of a uterine septum with a Nd:YAG laser was performed by Choe in 1992. Fedele and colleagues used an argon laser to resect a uterine septum in 1993 [13,14].…”
Section: Development Of Hysteroscopy In the Second Half Of The 20th Cmentioning
confidence: 99%
“…B. Kalpana 1 , Richa Gupta 2 1 HOD (Consultant), Department of Reproductive Medicine, Guru Hospital, Madurai. 2 Junior Consultant, Department of Reproductive Medicine, Guru Hospital, Madurai.…”
Section: Rare Case Reports Of Complete Uterine Septum With Longitudinmentioning
confidence: 99%
“…Kalpana 1 , Richa Gupta 2 1 HOD (Consultant), Department of Reproductive Medicine, Guru Hospital, Madurai. 2 Junior Consultant, Department of Reproductive Medicine, Guru Hospital, Madurai. HOW TO CITE THIS ARTICLE: Kalpana B, Gupta R. Rare case reports of complete uterine septum with longitudinal vaginal septum presenting as didelphic/ unicornuate uterus.…”
Section: Rare Case Reports Of Complete Uterine Septum With Longitudinmentioning
confidence: 99%